Designation and description of a neotype of Sclerophrys maculata (Hallowell, 1854), and reinstatement of S. pusilla (Mertens, 1937) (Amphibia: Anura: Bufonidae) - Poynton, John C.; Loader, Simon P.; Conradie, Werner; Rödel, Mark-Oliver; Liedtke, H. Christoph (Zootaxa, 2016)
Molecular analysis indicates that African material previously referred to Amietophrynus maculatus (Hallowell, 1854; now Sclerophrys maculata), is divisible into two distinct clades: a Western Clade from Cameroon westwards and an Eastern Clade from Central African Republic eastwards, and Uganda southwards to South Africa, extending to Angola-Namibia. Preliminary morphological and bioacoustic data support this division. The two clades are recognised here as two separate species. The Western species retains the name S. maculata, with Hallowell’s designated type locality of Liberia. The Eastern Clade retains the name published by Mertens (1937), S. pusilla. It is noted that a type specimen of S. maculata cannot be traced and is presumed lost; the so-called syntypes in the Philadelphia Academy of Natural Sciences are not the material described by Hallowell. None of these have been designated as a neotype, consequently a specimen from Liberia in the collection of the Natural History Museum, London, is designated here as the neotype of S. maculata.